Tinjauan Yuridis terhadap Implementasi Fatwa DSN-MUI Mengenai Pembiayaan Murabahan dalam Praktik Perbankan Syariah di Indonesia - Muiz, Abdul (Program Studi Perbankan Syariah STAI Senori Tuban, 2024)
The development of sharia banking in Indonesia has shown significant progress in the last few decades, with murabahah financing as one of the superior products in great demand by the public. This financing is considered easy and by Islamic economic principles, offers a solution for customers to obtain goods or services without having to pay in cash. The Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) plays an important role as a guideline in the implementation of murabahah products, ensuring that transactions are carried out transparently and fairly, under the provisions. This research uses a descriptive qualitative approach to analyze the implementation of the DSN-MUI fatwa regarding murabahah financing in Sharia banking practices. The research results show that although the DSN-MUI fatwa provides a clear legal framework, challenges in harmonizing the provisions of the fatwa and existing regulations are still an obstacle in the implementation of murabahah financing. Therefore, understanding and compliance of Sharia financial institutions with Sharia principles, as well as the role of the Sharia Supervisory Board (DPS) in supervision, is very important to maintain the integrity and trust of the public in Sharia banking products.